PALEO-CHANNELS OF SINGKAWANG WATERS WEST KALIMANTAN AND ITS RELATION TO THE OCCURRENCES OF SUB-SEABOTTOM GOLD PLACERS BASED ON STRATA BOX SEISMIC RECORD ANALYSES - Hananto Kurnio; Noor C.D. Aryanto (Marine Geological Institute of Indonesia, 2010)
Strata box seismic records were used to analyze sub-seabottom paleochannels in Singkawang Waters, West Kalimantan. Based on the analyses, it can be identified the distribution and patterns of paleochannels. Paleo channel at northern part of study area interpreted as a continuation of Recent coastal rivers; and at the southern part, the pattern radiates surround the cone-shaped morphology of islands, especially Kabung and Lemukutan Islands. Paleochannels of the study area belong to northwest Sunda Shelf systems that terminated to the South China Sea. A study on sequence stratigraphy was carried out to better understanding sedimentary sequences in the paleochannels. This study is also capable of identifying placer deposits within the channels. Based on criterias of gold placer occurrence such as existence of primary gold sources, intense chemical and physical weathering to liberate gold grains from their source rocks of Sintang Intrusive. Gravity transportation that involved water media, stable bed rock and surface conditions, caused offshore area of Singkawang fulfill requirements for gold placer accumulations. Chemical and physical whethering proccesses from Oligocene to Recent, approximately 36 million, might be found accumulation of gold placer on the seafloor. Based on grain size analyses, the study area consisted of sand 43.4%, silt 54.3% and clay 2.3%. Petrographic examination of the sample shows gold grains about 0.2%. Keywords: paleochannels, strata box seismic records, gold placer. Rekaman seismik strata box digunakan untuk menganalisa sungai purba bawah permukaan di Perairan Singkawang, Kalimantan Barat. Berdasarkan hasil analisis data strata box dapat diidentifikasi sebaran dan pola sungai purba. Sungai purba di bagian utara daerah penelitian ditafsirkan sebagai kelanjutan sungai sekarang, dan di selatan sungainya berpola memancar yang berasal dari pulau-pulau bermorfologi kerucut, seperti Pulau Kabung dan Lemukutan. Sungai purba daerah penelitian termasuk pada sistem sungai purba Paparan Sunda barat laut berakhir di Laut Cina Selatan. Suatu kajian sekuen stratigrafi dilaksanakan untuk lebih memahami sekuen-sekuen sedimen dalam sungai purba. Kajian ini juga mampu mengidentifikasi endapan-endapan plaser dalam alur tersebut. Berdasarkan kriteria pembentukan emas plaser atau letakan, seperti terdapatnya sumber emas primer, pelapukan kimia dan fisika yang sangat intensif untuk membebaskan butiran-butiran emas dari batuan induknya yaitu Batuan Terobosan Sintang. Transportasi gaya berat yang melibatkan media air, kondisi batuan dasar dan permukaan yang stabil, membuat daerah lepas pantai Singkawang memenuhi kriteria untuk akumulasi emas letakan. Proses pelapukan kimia dan fisika mulai dari Oligosen hingga Resen, sekitar 36 juta tahun memungkinkan dijumpainya akumulasi emas letakan di dasar laut. Berdasarkan hasil analisa besar butir daerah penelitian terdiri dari pasir 43,4%, lanau 54,3% dan lempung 2,3 %. Uji petrogafi menunjukan kandungan emas sekitar 0,2%. Kata kunci: sungai purba, rekaman seismik strata box, emas letakan.